Heat spreader featuring matched coefficient of thermal expansion and heat dissipation therewith

The copper composite heat spreader addresses inefficient thermal communication in electronic devices by matching CTE and enhancing heat dissipation, reducing thermomechanical stresses and improving reliability.

JP2024546518AActive Publication Date: 2024-12-25KUPRION INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024527486
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-18
Filing Date
2022-11-17
Publication Date
2024-12-25
Estimated Expiration
2042-11-17

AI Technical Summary

Technical Problem

Inefficient thermal communication between heat sources and heat sinks in electronic devices, particularly in components like high-power LEDs, high-power circuits, PCBs, and SIP systems, leads to excessive heat accumulation, which can cause overheating, substrate burnout, and circuit failure due to CTE mismatches and inadequate heat dissipation techniques such as thermal vias and coins.

Method used

A heat spreader with a copper composite surface, formed from metal nanoparticles and CTE modifiers, is used to match the thermal expansion coefficient of heat-generating components, ensuring effective thermal communication and reducing thermomechanical stresses by direct metallurgical bonding without the need for thermal grease.

Benefits of technology

The copper composite heat spreader enhances heat dissipation, reduces thermomechanical stresses, and improves the reliability and performance of electronic devices by maintaining contact with heat-generating components even under severe thermal cycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546518000001_ABST
    Figure 2024546518000001_ABST
Patent Text Reader

Abstract

The heat spreader may be tailored to match the coefficient of thermal expansion (CTE) to an electronic component or other heat generating component in thermal communication with the electronic component. In some cases, the heat generating component may be bonded to the heat spreader while achieving a CTE match. The copper nanoparticles may be consolidated with a CTE adjuster under mild conditions to define a heat spreader configured to contact a heat source and a heat sink, at least a portion of the heat spreader including a copper composite including a CTE adjuster. The copper composite may be present in or in a coating on a thermal conductor that defines the heat spreader. The copper composite may contact the heat generating component to promote effective heat transfer and a strong bond between the copper composite and the heat generating component, such as in a printed circuit board (PCB), followed by dissipation of the heat to a heat sink or other heat receiving structure.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Inefficient thermal communication between heat sources and heat sinks can hinder the dissipation of excess heat from systems, especially within electronic devices. For example, heat-generating electronic components, such as high-power LEDs and high-power circuits, are continually becoming smaller and more powerful, thereby generating excess heat loads that are increasingly concentrated in ever-decreasing spaces. Increasing levels of integration and complex electronic packaging in system-in-package (SIP) systems can also make heat dissipation difficult. The increased and concentrated excess heat generation can make effective heat removal particularly difficult to address, although important. Failure to remove excess heat from electronic devices can result in serious consequences, such as overheating, poor conduction, higher-than-normal power requirements, and / or the need for clock-down operation to avoid board burnout and device failure due to the presence of hot spots. Failure modes can include lateral displacement forces resulting from coefficient of thermal expansion (CTE) mismatch that can exceed bond line strength, leading to circuit destruction and / or shorting.

[0002] Ineffective heat conduction can be particularly ubiquitous in various types of circuit boards, especially printed circuit boards (PCBs), composite packaging, laminate boards, and system-in-package (SIP) components. PCBs and similar circuit boards are thermal insulators by the very nature of their construction. Specifically, PCBs may use thermally insulating substrates (e.g., fiberglass epoxy composites such as FR4, a common example having a thermal conductivity value of only 0.25 W / m·K) on which suitable electronic circuits and various board components are placed. The low thermal conductivity value of PCB substrates can make the removal of excess heat from electronic devices quite difficult. Because the leads or embedded metal traces are typically small in size, very little excess heat can be removed through them. Furthermore, traditional lead solders are not particularly thermally conductive (e.g., about one-tenth the thermal conductivity of more thermally conductive metals such as copper). th(See below.) For example, packaging substrates with heat slugs for GaN and SiC devices, monolithic microwave integrated circuits (MMICs), phased arrays, etc., as found in 5G base stations and power converters, can have similar problems. EMI shielding can have related problems, but without the occurrence of short circuits.

[0003] Thermal vias are one approach to remove excess heat generated by electronic components associated with a printed circuit board or similar structure. However, direct liquid casting of high melting point metals into the vias is not compatible with currently used board materials (metal processing temperatures >1000°C compared to the much lower polymer melting points of materials typically used as PCB substrates). o C). Thus, vias are often filled with rosin or a similar filler and then either galvanically capped on both ends or left open with only a thick metal plating (e.g., copper) formed on the via walls (i.e., via barrel) to facilitate electrical communication through the PCB substrate. This approach is done by slow electrodeposition and can result in suboptimal thermal communication by leaving gaps in the metal plug extending through the PCB. An alternative approach to fill vias using metal nanoparticles is described in U.S. Pat. No. 1,061,6994, incorporated herein by reference, which can facilitate more complete filling of the via holes and result in higher thermal conductivity. Large diameter vias can be compatible with such processes to provide more effective removal of excess heat. Even thermal vias can be insufficient to remove large amounts of excess heat.

[0004] Thermal coins are another approach for heat dissipation that can be used when more thermal conduction is needed than thermal vias can provide. Thermal coins are 3-4 mm diameter metal bodies that are pressed into the plane of a PCB or similar substrate. As a result of increased thermal conduction for thermal vias, size mismatches can be common and the thickness of the PCB during fabrication and the prefabricated thermal coins can vary, which can cause assembly problems when stacking multiple PCB layers together. Thermal coins are also typically manufactured in a limited range of shapes, which may not be applicable for certain PCB architectures.

[0005] Heat pipes are an alternative heat transfer medium that can facilitate the transfer of very large amounts of excess heat. While highly thermally conductive metals such as copper can only have thermal conductivity values ​​in the range of a few hundred W / m·K, heat pipes can provide much higher effective thermal conductivity values ​​in the range of several thousand W / m·K, such as about 10,000 W / m·K to about 100,000 W / m·K. Heat pipes function through direct heat transfer to a working fluid contained within an enclosed vessel, where conduction is further supplemented by the liquid-vapor phase transition and subsequent condensation of the working fluid. Heat pipes have traditionally been utilized in applications where passive dissipation of heat in harsh operating environments is desirable. Examples include satellite and spacecraft applications. Miniaturized heat pipes, such as oscillating heat pipes, have been used more recently to dissipate excess heat from printed circuit boards and similar small heat-generating electronic components.

[0006] Similar to a heat pipe, a heat spreader may also facilitate the dissipation of excess heat from a heat source in contact with it. Instead of the working fluid of a heat pipe, a heat spreader may facilitate the lateral diffusion of heat through a monolithic thermal conductor to facilitate more effective rejection of the excess heat to a thermal reservoir. A heat spreader may be tapered to facilitate the dissipation of excess heat from a heat source having a limited size, such as a point-like heat source, to a more widely spread dissipating surface, typically at or adjacent to a heat sink.

[0007] A difficulty associated with both heat pipes and heat spreaders is that ineffective thermal communication may exist between the heat generating component and the outer surface of the heat pipe or heat spreader due to coefficient of thermal expansion (CTE) mismatch. For example, copper is a highly thermally conductive metal that is often utilized to form the outer shell of a heat pipe or to form the monolithic metal body of a heat spreader, but this metal has a significantly different CTE than the ceramic materials that are typically present in heat generating components of a printed circuit board or similar components that generate excess heat. The CTE mismatch may lead to disengagement of the heat generating component from the heat pipe or heat spreader when heat is generated, thereby significantly negating the ability of the heat pipe or heat spreader to dissipate excess heat from the heat generating component. Disengagement of the heat spreader from a heat sink or other heat receiving structure may be problematic as well. Additionally, the material used to bond the heat pipe or heat spreader to the heat generating component may also further contribute to the CTE mismatch. [Brief description of the drawings]

[0008] The following figures are included to illustrate certain aspects of the disclosure and should not be viewed as exclusive embodiments. The disclosed subject matter is capable of significant modification, permutations, combinations, and equivalents in form and function, as will occur to those skilled in the art and having the benefit of this disclosure. [Figure 1] FIG. 1 shows a diagram of the proposed structure of metal nanoparticles with a surfactant coating on their surface. [Diagram 2] FIG. 1 shows a diagram of the proposed structure of metal nanoparticles with a surfactant coating on their surface. [Figure 3A] 1A-1D show cross-sectional views of various configurations of the heat spreader of the present disclosure. [Figure 3B] 1A-1D show cross-sectional views of various configurations of the heat spreader of the present disclosure. [Figure 3C] 1A-1D show cross-sectional views of various configurations of the heat spreader of the present disclosure. [Figure 3D] 1A-1D show cross-sectional views of various configurations of the heat spreader of the present disclosure. [Figure 4] 1 shows a diagram of an exemplary heat spreader in which multiple conductive fibers extend from a coating on one end of a thermal conductor. [Diagram 5] 1 shows a diagram in which a heat spreader is bonded to the top surface of a heat generating component. [Figure 6] 1 shows a diagram in which a heat spreader is bonded to the bottom surface of a heat generating component. [Figure 7] 1 shows a diagram in which a heat spreader is bonded to the top and bottom surfaces of a heat generating component. [Figure 8] A diagram showing multiple heat spreaders bonded to the sides of a heat-generating component. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present disclosure relates generally to thermal management, and more specifically to a heat spreader having at least an outer surface with an improved coefficient of thermal expansion (CTE) that matches heat generating components used in printed circuit boards (PCBs) and related electronic devices, such as copper clad substrates (CCBs) and substrates employing novel ceramics such as AlN and SiN. The heat generating components may use electrically and thermally insulating substrates such as FR4 or other polymer substrates, or in some cases, electrically insulating but thermally conductive substrates such as AlN. Advantageously, the present disclosure may facilitate tailoring the CTE of at least the outer surface of the heat spreader to match the CTE of a given heat generating component. A CTE that matches the CTE of a heat sink or similar heat receiving structure may also be achieved. The heat spreader may be attached directly to the backside of a PCB, either as a monolithic thermal ground plane or as a finned heat sink. Direct metal bonding may be achieved in some system architectures using a bonding layer between the heat spreader and the heat generating component, resulting in mechanical durability. Additionally, the heat spreaders and related concepts of the present disclosure may avoid or minimize the use of thermal grease and gel pads that may be required to mitigate CTE mismatch, even at the cost of less effective thermal conductivity. CTE tuning may be accomplished in a variety of ways, as described below.

[0010] As mentioned above, the removal of excess heat from heat generating components of circuit boards and associated electronic assemblies can be difficult to solve due to the ubiquity of insulating materials therein. Heat spreaders can be effective in dissipating large amounts of excess heat from such systems, but the CTE mismatch between the metal components of the heat spreader and various portions of the electronic components or other heat generating structures can be significant, especially those that include non-metallic components such as various ceramics. CTE mismatch can be ubiquitous in heat generating components that feature both insulating and thermally conductive substrates such as AlN and SiN. If excessive CTE mismatch exists in either type of system, the heat spreader can separate from the heat generating component upon heat generation, thereby negating or severely limiting the ability of the heat spreader to dissipate excess heat, resulting in overheating and burning of the heat generating component.

[0011] The present disclosure provides a heat spreader that may provide a more effective CTE match between at least an outer surface of the heat spreader and a heat generating component. More specifically, the present disclosure provides a metal composite including a CTE modifier, such as a copper composite, that may define at least an outer surface of the heat spreader, and optionally a larger portion or even the entire heat spreader. The metal composite may be formed using metal nanoparticles, such as copper nanoparticles, consolidated together to form a bulk metal having a low degree of nanoporosity. Even before CTE tuning, the fused copper nanoparticles have a relatively low CTE of only about 7-11 ppm (varies based on the degree of nanoporosity present), which may be further tuned in the copper composite using at least one CTE modifier, as further described herein. The CTE of the metal composite may be readily altered by adjusting the loading of the CTE modifier in the continuous metal matrix to promote a more effective CTE match with the ceramic material in the heat generating component, such as those containing SiC, GaN, AlN, and the like. Metal composites can be readily formed from compositions including metal nanoparticles, such as copper nanoparticles, such that the metal composite and heat spreader can be formed by solid state sintering at low temperatures, well below the melting point of the molten metal. Heat sinks or similar heat receiving structures may be similarly CTE matched to heat spreaders by similarly utilizing metal nanoparticles and CTE modifiers at their locations. Further details regarding metal nanoparticles, such as copper nanoparticles, and properties that may facilitate low temperature processing are described below.

[0012] A suitable CTE modifier can reduce the already low CTE (7-11 ppm) of bulk metals formed from copper nanoparticles to potentially as low as 3 ppm at room temperature, compared to values ​​of 17 ppm typically found in bulk copper. These features can greatly simplify PCB assemblies and other heat transfer architectures, resulting in overall product cost savings, while significantly improving performance and reliability in locations where severe thermal shock and significant thermal cycling occurs. Similarly, the CTE can be adjusted upwards by including bulk copper powder in the copper nanoparticle consolidation, including CTE values ​​approaching 17 ppm. If necessary, even higher CTE values ​​may be achieved by including micron-sized particles of other metals, such as aluminum particles, flakes or wires, in which case CTE values ​​approaching 23 ppm may be achieved. Thus, the metal composites of the present disclosure may be formed from copper nanoparticles and at least one CTE modifier, optionally further combined with bulk copper powder, to provide a range of achievable CTE values.

[0013] In addition to facilitating an improved CTE match between the heat spreader and the substrate of the electronic component or similar heat generating component, the metal nanoparticle composition may also facilitate a direct bond between the electronic component and the heat spreader by a bonding layer, similar to that produced by soldering or the use of a metal paste. For example, the metal nanoparticle composition may be applied as a bonding layer on a surface of the electronic component, and subsequent consolidation of the metal nanoparticles in the bonding layer may facilitate a direct metallurgical bond to at least a portion of the outer surface of the heat spreader, which is also formed from the consolidated metal nanoparticles. The direct metallurgical bond significantly reduces the likelihood of the heat generating component and the heat spreader disengaging from one another. Furthermore, because the heat spreader (or its outer coating) and the bonding layer may be formed from similar materials, there is less chance of a CTE mismatch, thereby limiting or even eliminating thermomechanical stresses. That is, the bonding layer may define a transition layer having an intermediate CTE between the electronic component and the outer surface of the heat spreader. With large electronic component sizes and high operating temperatures (e.g., below about 350° C.), even small CTE differences would result in high thermomechanical stress values ​​leading to potential delamination and device failure. CTE matching of the outer surface of the heat spreader to a heat sink or similar heat receiving structure may also be achieved by using metal nanoparticles and CTE modifiers to form at least a portion of the heat sink or similar heat receiving structure, possibly resulting in a metallurgical bond.

[0014] The heat spreaders of the present disclosure may be used in conjunction with printed circuit boards and similar architectures where heat generating electronic components are of concern. The heat spreaders may be connected to printed circuit boards and similar architectures in a variety of ways. Heat generating components located on or embedded within the surface of a printed circuit board may be connected to the heat spreaders of the present disclosure on the front side facing away from the non-conductive substrate of the PCB, on the side of the heat generating electronic components, and / or on the underside of the heat generating electronic components. In the latter configuration, the heat spreader may extend through the electrically insulating substrate of the PCB to contact the heat generating components. Combinations of the aforementioned heat spreader configurations may be used to provide multiple heat transfer paths. The aforementioned heat spreader configurations for connecting the heat spreader to the heat generating components may be utilized to facilitate stacking multiple printed circuit board layers on top of each other to provide three-dimensional integration of devices and systems such as SIPs on processors and memory devices. The heat spreader may be in thermal communication with a structure for eliminating excess heat shunted through it, for example, a liquid reservoir, radiator, or similar structure that acts as a heat sink. The heat spreader may optionally be in further thermal communication or physical contact with a heat pipe, which may carry excess heat further away from the heat-generating electronic components, i.e., the heat pipe may be between the heat spreader and the heat sink.

[0015] Similarly, for heat generating components featuring an electrically insulating but highly thermally conductive substrate such as AlN or SiN, the heat spreader of the present disclosure may be disposed on either side of the substrate or at least partially within the substrate. When an electrically insulating but thermally conductive substrate is used, the heat spreader may be in thermal communication with the heat generating component through the thermally conductive substrate rather than in direct contact with the heat generating component. In some cases, AlN or SiN may be deposited as a thin film (e.g., about 300 microns to about 500 microns thick) on the surface of an electrically insulating substrate to impart thermal conductivity to the surface. The heat spreaders of the present disclosure may be used in these configurations as well.

[0016] Metal nanoparticles are uniquely suited to form at least a surface coating on a heat spreader, or optionally the entire heat spreader. At the very least, the heat spreader may be better CTE matched to a heat generating component having a low CTE, and if a bonding layer is further utilized, the bonding layer may provide a strong bonding interaction between the heat spreader and the heat generating component, or the bonding layer may have a CTE intermediate between the CTE of the heat generating component and the CTE of the heat spreader. Moderate processing conditions to consolidate the metal nanoparticles to form a bulk metal (e.g., bulk copper) in a metal composite with low nanoporosity (e.g., a copper composite with a CTE modifier) ​​may facilitate the formation of the bonding layer and other optional components of the heat spreader. As described in more detail below, the metal nanoparticles can be consolidated (fused) together into the corresponding bulk metal under a range of mild processing conditions well below the melting point of the metal itself. Due to the high thermal conductivity and relatively low cost of copper, copper nanoparticles may be a particularly desirable type of metal nanoparticle for use in various embodiments of the present disclosure. Bulk copper formed from metal nanoparticles combined with CTE modifiers may effectively form a well-dispersed composite after metal nanoparticle consolidation. Suitable CTE modifiers may include, for example, carbon fibers, diamond particles, boron nitride particles or fibers, carbon nanotubes, graphene, W and / or Mo particles, silicon particles, graphite powder, silicon nitride particles or fibers, aluminum nitride particles or fibers, copper oxide nanoparticles, and any combination thereof. W and / or Mo particles may also impart oxidation resistance to copper. In addition to promoting CTE matching between the surface of the heat spreader and the heat generating components, the CTE modifiers and optional micron-sized metal particles may also limit shrinkage during consolidation of the metal nanoparticles, which may exceed 20% for other metal nanoparticle systems. Limited shrinkage may help to alleviate thermomechanical stresses during operational high-low temperature cycles that occur during use of the heat spreader. Additionally, the nanoporosity obtained after metal nanoparticle consolidation may impart additional flexibility that may provide additional resistance to thermomechanical stresses.

[0017] In addition to the aforementioned advantages, the metal nanoparticles may facilitate the manufacture of a heat spreader having an improved structure for dissipating heat from the heat spreader. For example, some heat spreaders of the present disclosure may include a plurality of thermally conductive fibers extending from an end (cold end) of the heat spreader that may facilitate rapid dissipation of excess heat to a heat sink, such as the surrounding atmosphere, a marine environment (e.g., ocean, lake, or river water), or a radiator for space applications. The conductive fibers may be bonded to the heat spreader using a metal nanoparticle composition that is also effective in promoting CTE matching, as briefly described above and described in more detail below. Bonding of the conductive fibers may be achieved during the manufacture of the heat spreader without a separate bonding step by incorporating the ends of the conductive fibers into a suitable metal nanoparticle composition before consolidation of the metal nanoparticles occurs. Following consolidation of the metal nanoparticles, one set of the conductive fiber ends remains firmly anchored within the resulting metal composite, while the other set of the conductive fiber ends extends outwardly from the heat spreader to facilitate heat dissipation from the heat spreader.

[0018] As used herein, the term "metal nanoparticle" refers to metal particles having a size of about 200 nm or less, without particular reference to the shape of the metal particle.

[0019] As used herein, the term "micron-scale metal particles" refers to metal particles having a size in at least one dimension of about 200 nm or greater.

[0020] The terms "consolidate," "consolidation," and other variations thereof are used interchangeably herein with the terms "fuse," "fusion," and other variations thereof.

[0021] As used herein, the terms "partially fused", "partial fusion", and other derivatives and grammatical equivalents refer to the partial coalescence of metal nanoparticles together. Totally fused metal nanoparticles retain only the minimal structural morphology of the original non-fused metal nanoparticles (i.e., they resemble dense bulk metal but exhibit internal particle sizes in the range of 100-500 nm with low nanoporosity), whereas partially fused metal nanoparticles retain at least a portion of the structural morphology of the original non-fused metal nanoparticles, e.g., higher levels of porosity, smaller average particle size, and more grain boundaries. The properties of partially fused metal nanoparticles can be intermediate between those of the corresponding bulk metal and the original non-fused metal nanoparticles. In some embodiments, a fully dense (non-porous) bulk metal can be obtained after consolidation of the metal nanoparticles to obtain a metal composite. In other embodiments, the metal composite may have less than about 10% porosity, or less than about 20% porosity, or less than about 30% porosity, at amounts greater than full densification (i.e., >0% porosity). Thus, in certain embodiments, a metal composite formed from metal nanoparticles and a CTE modifier may have a porosity (nanoporosity) in the range of about 2% to about 30%, or about 2% to about 5%, or about 5% to about 10%, or about 10% to about 15%, or about 15% to about 20%, or about 20% to about 25%, or about 25% to about 30%.

[0022] Before further describing more specific aspects of the present disclosure in more detail, an additional brief description of metal nanoparticles and their processing conditions, particularly copper nanoparticles, is first provided. Metal nanoparticles exhibit several properties that may be significantly different from those of the corresponding bulk metal. One property of metal nanoparticles that may be particularly important for processing according to the present disclosure is nanoparticle fusion (consolidation) that occurs at the melting temperature of the metal nanoparticles. As used herein, the term "fusion temperature" refers to the temperature at which the metal nanoparticles liquefy, thereby giving the appearance of melting. As used herein, the terms "fusion" and "consolidation" synonymously refer to the coalescence or partial coalescence of metal nanoparticles with each other to form a larger mass, such as a bonded interface or metal composite, on at least the outer surface of the heat spreader. The melting temperature may be as much as 80% below the melting point of the corresponding bulk metal. Thus, at least partial connectivity exists between the metal nanoparticles after heating above the melting temperature. After consolidation of the metal nanoparticles, the resulting nanoporosity can accommodate thermal stresses that arise during heating and cooling cycles. Without wishing to be bound by theory or mechanism, it is believed that the nanoporosity may absorb stresses resulting from the expansion or contraction of the heat spreader, rather than suffering from failure from the rapid release of thermo-mechanical stresses.

[0023] As size decreases, especially below about 20 nm in equivalent spherical diameter, the temperature at which metal nanoparticles liquefy drops dramatically from that of the corresponding bulk metal. o For example, copper nanoparticles having a size of about 20 nm or less have a melting point of about 235 C, compared to the melting point of bulk copper. o C or less, or about 220 o C or less, or about 200 o The metal nanoparticles can have a melting temperature below 375° C. Thus, consolidation of the metal nanoparticles occurring at the melting temperature can allow for the production of structures containing the bulk metal at significantly lower processing temperatures than would be possible if the bulk metal itself were directly processed as the starting material. Processing conditions for consolidating the metal nanoparticles are typically around 375° C. oF (190.6°C), or even below about 450°F (232.2°C), and within the normal PCB manufacturing parameters of 275 to 400 psi, but pressure is not necessarily required for metal nanoparticle fusion to occur. Higher density bulk metal may be obtained by applying pressure when promoting consolidation of the metal nanoparticles. Thus, in some cases, pressures as high as up to about 1500 psi may be applied to the metal nanoparticles to promote consolidation. For example, for copper nanoparticles, the melting temperature (below about 220°C) is below the temperature at which commonly used PCB substrates melt or deform. Thus, copper nanoparticle fusion may occur in conjunction with temperature conditions used in conventional PCB manufacturing processes, although more vigorous consolidation conditions may optionally be used. Fusion may be performed under an inert atmosphere to prevent metal oxidation, or in the case of larger surfaces or articles, there may be sufficient outgassing to limit oxidation even in the absence of an inert atmosphere. Thus, metal nanoparticles such as copper nanoparticles provide an easy to handle material for forming the bulk metal of a metal composite within at least a portion of a heat spreader or within at least a portion of a bonding layer on a heat spreader, particularly when incorporating the heat spreader within a PCB manufacturing process.

[0024] A number of scalable processes have been developed for producing large quantities of metal nanoparticles within a target size range. Most typically, such processes for producing metal nanoparticles are carried out by reducing a metal precursor in the presence of one or more surfactants. The metal nanoparticles can then be isolated and purified from the reaction mixture by common isolation techniques and processed into a formulation suitable for distribution.

[0025] Any suitable technique can be used to form the metal nanoparticles used in the disclosure of this specification. Particularly easy metal nanoparticle manufacturing techniques are described in U.S. Patent Nos. 7,736,414, 8,105,414, 8,192,866, 8,486,305, 8,834,747, 9,005,483, 9,095,898, and 9,700,940, each of which is incorporated herein by reference in its entirety. As described therein, metal nanoparticles can be produced in a narrow size range by reducing a metal salt in a solvent in the presence of a suitable surfactant system, which can include one or more different surfactants. A target size distribution of metal nanoparticles, such as a bimodal size distribution, may be obtained by combining metal nanoparticles of different sizes together. Further description of suitable surfactant systems is provided below. Without being bound by any theory or mechanism, it is believed that the surfactant system can mediate the nucleation and growth of the metal nanoparticles, limit the surface oxidation of the metal nanoparticles, and / or inhibit the metal nanoparticles from extensively agglomerating together before at least partially fusing together. Suitable organic solvents for solubilizing the metal salts and forming the metal nanoparticles can include, for example, formamide, N,N-dimethylformamide, dimethylsulfoxide, dimethylpropyleneurea, hexamethylphosphoramide, tetrahydrofuran, glyme, diglyme, triglyme, tetraglyme, proglyme, or polyglyme. Suitable reducing agents for reducing the metal salts and promoting the formation of the metal nanoparticles can include, for example, alkali metals (e.g., lithium naphthalide, sodium naphthalide, or potassium naphthalide) or borohydride reducing agents (e.g., sodium borohydride, lithium borohydride, potassium borohydride, or tetraalkylammonium borohydride) in the presence of a suitable catalyst.

[0026] 1 and 2 show diagrams of the possible structure of a metal nanoparticle with a surfactant coating on its surface. As shown in FIG. 1, metal nanoparticle 10 includes metal core 12 and surfactant layer 14 overcoating metal core 12. Surfactant layer 14 can contain any combination of surfactants, as described in more detail below. Metal nanoparticle 20 shown in FIG. 2 is similar to that shown in FIG. 1, except that metal core 12 is grown around nucleus 21, which can be the same metal as that of metal core 12 or a different metal. Nucleus 21 is deeply embedded within metal core 12 in metal nanoparticle 20 and is very small in size, so it is not believed to significantly affect the overall nanoparticle properties. Nucleus 21 can include a salt or metal, which can be the same or different metal as metal core 12. In some embodiments, the nanoparticle can have an amorphous morphology.

[0027] As discussed above, the metal nanoparticles have a surfactant coating on their surface that contains one or more surfactants. The surfactant coating can be formed on the metal nanoparticles during synthesis of the metal nanoparticles. The surfactant coating is generally lost during consolidation of the metal nanoparticles upon heating above their melting temperature, resulting in the formation of a bulk metal with presumably uniform nanoporosity present therein. Forming a surfactant coating on the metal nanoparticles during synthesis of the metal nanoparticles can desirably limit the ability of the metal nanoparticles to prematurely fuse together, limit the aggregation of the metal nanoparticles, and promote the formation of a population of metal nanoparticles with a narrow size distribution. The porosity value can be in the range of about 2-30% or about 2-15% after consolidation, which can be adjusted based on several factors, including the type of surfactant(s) present and whether or not micron-scale metal particles contact the metal nanoparticles during consolidation. With nanoporosity of about 2% to about 15%, the copper composite may contain about 85% to 98% densely fused copper nanoparticles, with closed pore nanoporosity having pore sizes in the range of about 50 nm to about 500 nm, or about 100 nm to about 300 nm, or about 150 nm to about 250 nm.

[0028] The types of metal nanoparticles suitable for use with various embodiments of the present disclosure are not considered to be particularly limited. Suitable metal nanoparticles can include, but are not limited to, tin nanoparticles, copper nanoparticles, aluminum nanoparticles, palladium nanoparticles, silver nanoparticles, gold nanoparticles, iron nanoparticles, cobalt nanoparticles, nickel nanoparticles, titanium nanoparticles, zirconium nanoparticles, hafnium nanoparticles, tantalum nanoparticles, molybdenum nanoparticles, tungsten nanoparticles, and the like. Combinations of these metal nanoparticles may also be used. Micron-scale particles of these metals can be present in a metal nanoparticle paste composition that also contains metal nanoparticles. Copper can be a particularly desirable metal for use in embodiments of the present disclosure due to its low cost, strength, and excellent electrical and thermal conductivity values.

[0029] In various embodiments, the surfactant system present in the metal nanoparticles can include one or more surfactants. The different properties of various surfactants can be used to adjust the properties of the metal nanoparticles. Factors that can be taken into consideration when selecting a surfactant or a combination of surfactants to include on the metal nanoparticles include, for example, the ease of dissipation of the surfactant from the metal nanoparticles during nanoparticle fusion, the nucleation and growth rate of the metal nanoparticles, the metal content of the metal nanoparticles, etc.

[0030] In some embodiments, an amine surfactant or a combination of amine surfactants, particularly aliphatic amines, can be present on the metal nanoparticles. Amine surfactants can be particularly desirable for use with copper nanoparticles. In some embodiments, two amine surfactants can be used in combination with each other. In other embodiments, three amine surfactants can be used in combination with each other. In more specific embodiments, primary amines, secondary amines, and diamine chelators can be used in combination with each other. In even more specific embodiments, the three amine surfactants can include long chain primary amines, secondary amines, and diamines with at least one tertiary alkyl group nitrogen substituent. Further disclosure regarding suitable amine surfactants follows below.

[0031] In some embodiments, the surfactant system can include a primary alkylamine. In some embodiments, the primary alkylamine can be a C2-C 18 In some embodiments, the primary alkylamine is a C7-C 10 In other embodiments, C5-C6 primary alkylamines can also be used. Without being bound by any theory or mechanism, it is believed that the exact size of the primary alkylamine can be balanced between being long enough to provide an effective reverse micelle structure during synthesis, being easily volatile, and / or being easy to handle during nanoparticle compaction. For example, primary alkylamines having more than 18 carbons may also be suitable for use in the present embodiments, but may be more difficult to handle due to their waxy nature. In particular, C7-C 10 Primary alkyl amines can represent a good balance of desirable properties for ease of use.

[0032] In some embodiments, C2 to C 18The primary alkylamine can be, for example, n-hexylamine, n-heptylamine, n-octylamine, n-nonylamine, or n-decylamine. These are all linear primary alkylamines, but in other embodiments, branched primary alkylamines can also be used. For example, branched primary alkylamines can be used, such as 7-methyloctylamine, 2-methyloctylamine, or 7-methylnonylamine. In some embodiments, such branched primary alkylamines can be sterically hindered when they are attached to the nitrogen atom of the amine. Non-limiting examples of such sterically hindered primary alkylamines can include, for example, t-octylamine, 2-methylpentan-2-amine, 2-methylhexane-2-amine, 2-methylheptan-2-amine, 3-ethyloctane-3-amine, 3-ethylheptane-3-amine, 3-ethylhexane-3-amine, and the like. Additional branching can also be present. Without being bound by any theory or mechanism, it is believed that primary alkylamines can act as ligands in the metal coordination sphere, but can easily dissociate from the metal coordination sphere during compaction of the metal nanoparticles.

[0033] In some embodiments, the surfactant system can include a secondary amine. Secondary amines suitable for forming metal nanoparticles can include linear, branched, or cyclic C4-C bonded to the nitrogen atom of the amine. 12 The secondary amines may include alkyl groups. In some embodiments, branching may occur on the carbon atom attached to the nitrogen atom of the amine, thereby causing significant steric hindrance at the nitrogen atom. Suitable secondary amines may include, but are not limited to, dihexylamine, diisobutylamine, di-t-butylamine, dineopentylamine, di-t-pentylamine, dicyclopentylamine, dicyclohexylamine, and the like. C4-C 12Secondary amines outside the above range can also be used, however, such secondary amines may have undesirable physical properties such as low boiling points or waxy consistency that can complicate their handling.

[0034] In some embodiments, the surfactant system can include a chelating agent, particularly a diamine chelating agent. In some embodiments, one or both of the nitrogen atoms of the diamine chelating agent can be substituted with one or two alkyl groups. When two alkyl groups are present on the same nitrogen atom, the two alkyl groups can be the same or different. Furthermore, when both nitrogen atoms are substituted, the same alkyl groups can be present or different alkyl groups can be present. In some embodiments, the alkyl groups can be C1-C6 alkyl groups. In other embodiments, the alkyl groups can be C1-C4 alkyl groups or C3-C6 alkyl groups. In some embodiments, the C3 or higher alkyl groups can be linear or branched. In some embodiments, the C3 or higher alkyl groups can be cyclic. Without being bound by any theory or mechanism, it is believed that the diamine chelating agent can facilitate the formation of metal nanoparticles by facilitating the nucleation of nanoparticles.

[0035] In some embodiments, suitable diamine chelating agents may include N,N'-dialkylethylenediamines, particularly C1-C4 N,N'-dialkylethylenediamines. Corresponding methylenediamine, propylenediamine, butylenediamine, pentylenediamine or hexylenediamine derivatives may also be used. The alkyl groups may be the same or different. C1-C4 alkyl groups that may be present may include, for example, methyl, ethyl, propyl, and butyl groups, or branched alkyl groups such as isopropyl, isobutyl, s-butyl, and t-butyl groups. Exemplary N,N'-dialkylethylenediamines that may be suitable for inclusion on the metal nanoparticles may include, for example, N,N'-di-t-butylethylenediamine, N,N'-diisopropylethylenediamine, and the like.

[0036] In some embodiments, suitable diamine chelating agents may include N,N,N',N'-tetraalkylethylenediamines, particularly C1-C4N,N,N',N'-tetraalkylethylenediamines. Corresponding methylenediamine, propylenediamine, butylenediamine, pentylenediamine or hexylenediamine derivatives may also be used. The alkyl groups may similarly be the same or different and may include those mentioned above. Exemplary N,N,N',N'-tetraalkylethylenediamines that may be suitable for use in forming metal nanoparticles may include, for example, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, and the like.

[0037] Surfactants other than aliphatic amines can also be present in the surfactant system.In this regard, suitable surfactants can include, for example, pyridines, aromatic amines, phosphines, thiols, or any combination thereof.These surfactants can be used in combination with aliphatic amines such as those mentioned above, or can be used in surfactant systems that do not have aliphatic amines.Further disclosure regarding suitable pyridines, aromatic amines, phosphines, and thiols follows below.

[0038] Suitable aromatic amines include ArNR 1 R 2 where Ar is a substituted or unsubstituted aryl group and R 1 and R 2 are the same or different. R 1 and R 2 can be independently selected from H or an alkyl or aryl group containing 1 to about 16 carbon atoms. Exemplary aromatic amines that may be suitable for use in forming metal nanoparticles include, for example, aniline, toluidine, anisidine, N,N-dimethylaniline, N,N-diethylaniline, and the like. Other aromatic amines that can be used in conjunction with metal nanoparticles can be envisioned by one of ordinary skill in the art.

[0039] Suitable pyridines include both pyridine and its derivatives. Exemplary pyridines that may be suitable for inclusion on metal nanoparticles include, for example, pyridine, 2-methylpyridine, 2,6-dimethylpyridine, collidine, pyridazine, etc. Chelating pyridines, such as bipyridyl chelators, may also be used. Other pyridines that may be used with metal nanoparticles may be envisioned by those skilled in the art.

[0040] Suitable phosphines can have the formula PR3, where R is an alkyl or aryl group containing 1 to about 16 carbon atoms. The alkyl or aryl groups attached to the phosphorus center can be the same or different. Exemplary phosphines that can be present on the metal nanoparticles include, for example, trimethylphosphine, triethylphosphine, tributylphosphine, tri-t-butylphosphine, trioctylphosphine, triphenylphosphine, and the like. Phosphine oxides can be used as well. In some embodiments, surfactants containing two or more phosphine groups configured to form a chelating ring can also be used. Exemplary chelating phosphines can include, for example, bisphosphines such as 1,2-bisphosphine, 1,3-bisphosphine, and BINAP. Other phosphines that can be used in conjunction with the metal nanoparticles can be envisioned by one of skill in the art.

[0041] Suitable thiols can have the formula RSH, where R is an alkyl or aryl group having about 4 to about 16 carbon atoms. Exemplary thiols that can be present on the metal nanoparticles include, for example, butanethiol, 2-methyl-2-propanethiol, hexanethiol, octanethiol, benzenethiol, and the like. In some embodiments, surfactants containing two or more thiol groups configured to form a chelating ring can also be used. Exemplary chelating thiols can include, for example, 1,2-dithiols (e.g., 1,2-ethanethiol) and 1,3-dithiols (e.g., 1,3-propanethiol). Other thiols that can be used in conjunction with the metal nanoparticles can be envisioned by one of ordinary skill in the art.

[0042] As mentioned above, a distinguishing feature of metal nanoparticles is their low melting temperature, which may facilitate consolidation to form bulk metal within the metal composites disclosed herein. To facilitate distribution of the metal nanoparticles, the metal nanoparticles may be incorporated into a paste or similar formulation. Additional disclosure regarding metal nanoparticle paste compositions and similar formulations follows below.

[0043] Metal nanoparticle paste compositions or similar formulations can be prepared by dispersing as-produced or as-isolated metal nanoparticles in an organic matrix containing one or more organic solvents and various other optional ingredients. As used herein, the terms "nanoparticle paste formulation", "nanoparticle paste composition", "nanoparticle paste" and their grammatical equivalents are used interchangeably and refer synonymously to a fluid composition containing dispersed metal nanoparticles suitable for dispensing using a desired technique. The use of the term "paste" does not necessarily imply adhesive functionality of the paste alone. Judicious selection of organic solvent(s) and other additives allows for the addition of metal nanoparticles, etc., easy dispensing of the metal nanoparticles, and formation of bulk metal.

[0044] Cracks may sometimes occur during consolidation of metal nanoparticles. One way in which the nanoparticle paste of the present disclosure can facilitate reducing the degree of cracking and void formation after metal nanoparticle consolidation is by maintaining a high solids content. More specifically, in some embodiments, the paste composition can contain at least about 30% metal nanoparticles by weight, particularly about 30% to about 98% metal nanoparticles by weight of the paste composition, or about 50% to about 95% metal nanoparticles by weight of the paste composition, or about 70% to about 98% metal nanoparticles by weight of the paste composition, or about 85% to about 98% metal nanoparticles by weight of the paste composition, or about 88% to about 99% metal nanoparticles by weight of the paste composition. Furthermore, in some embodiments, in addition to the metal nanoparticles, small amounts (e.g., about 0.01% to about 15% by weight or about 35% by weight or about 60% by weight of the paste composition) of micron-scale particles, particularly micron-scale metal particles, can be present. The micron-scale metal particles may include any of particulate materials, fibers, and / or flakes. Such micron-scale metal particles can desirably facilitate the fusion of the metal nanoparticles into a continuous mass of bulk metal, further reducing the incidence of cracking. Instead of being liquefied and directly consolidated as in the case of metal nanoparticles, the micron-scale metal particles can simply bond together when in contact with the liquefied metal nanoparticles that have been elevated above their melting temperature. These factors can reduce the porosity that occurs after the metal nanoparticles are fused together. The micron-scale metal particles can contain the same or different metal as the metal nanoparticles, and suitable metals for the micron-scale metal particles can include, for example, copper, silver, gold, aluminum, tin, molybdenum, tungsten, and the like. In some embodiments, micron-scale graphite particles can also be included. In some embodiments, carbon nanotubes, boron nitride, diamond particles, and / or graphene can be included. According to some embodiments, the carbonaceous additive can increase the thermal conductivity that results after the consolidation of the metal nanoparticles has taken place. The micron-scale metal particles or similarly sized micron-scale additives can also function in the capacity of a CTE modifier.The CTE may be further tailored to facilitate CTE matching according to the present disclosure through the addition of various CTE adjusters. Any of the aforementioned micron-scale particles may further act as crack deflectors to limit crack propagation during use, thereby increasing mechanical strength.

[0045] The reduction of cracking and void formation during metal nanoparticle consolidation can also be promoted by judicious selection of the solvent(s) forming the organic matrix. A tailored combination of organic solvents can desirably reduce the incidence of cracking and void formation. More specifically, organic matrices containing one or more hydrocarbons (saturated, monounsaturated, polyunsaturated (two or more double bonds) or aromatic), one or more alcohols, one or more amines, and one or more organic acids can be particularly effective for this purpose. In some embodiments, one or more esters and / or one or more anhydrides may be included. In some cases, alkanolamines such as ethanolamine may be present. Without being bound by any theory or mechanism, it is believed that this combination of organic solvents can promote the removal and sequestering of surfactant molecules surrounding the metal nanoparticles during consolidation so that the metal nanoparticles can more easily fuse together. More specifically, it is believed that the hydrocarbon and alcohol solvents can passively solubilize surfactant molecules liberated from the metal nanoparticles by Brownian motion, reducing the ability of the surfactant molecules to reattach to the metal nanoparticles. In cooperation with the passive solubilization of the surfactant molecules, the amine solvents and organic acid solvents can actively sequester the surfactant molecules through chemical interactions such that they are no longer available to recombine with the metal nanoparticles.

[0046] Further adjustments to the solvent composition can be made to reduce the rapid volume shrinkage that occurs during surfactant removal and metal nanoparticle compaction. Specifically, two or more members of each class of organic solvents (i.e., hydrocarbons, alcohols, amines, and organic acids), optionally in combination with one or more alkanolamines, esters, or anhydrides, can be present in the organic matrix, with the members of each class having boiling points separated from one another by a set temperature. For example, in some embodiments, the various members of each class are about 20° apart from one another. o C~about 50 o By using such a solvent mixture, the various components of the solvent mixture can have a wide range of boiling points (e.g., about 50 o C ~ about 200 o C) can be removed gradually over time, minimizing sudden volume changes due to rapid loss of solvent during compaction of the metal nanoparticles.

[0047] In various embodiments, at least a portion of the one or more organic solvents is about 100 o In various other embodiments, at least a portion of the one or more organic solvents can have a boiling point of about 200 C or higher. o In some or other embodiments, the one or more organic solvents may have a boiling point of about 50 C or higher. o C ~ about 200 o C, or about 50 o C ~ approx. 250 o C, or about 50 o C ~ approx. 300 o C, or about 50 o C ~ approx. 350 o C, or about 50 o C ~ approx. 365 oThe organic solvents may have boiling points ranging from 0.1 to 1.0 C. The use of high boiling organic solvents can desirably increase the pot life of the metal nanoparticle paste composition and limit the rapid loss of solvent that may otherwise result in cracking and void formation during nanoparticle consolidation. In some embodiments, at least one of the organic solvents can have a boiling point higher than the boiling point(s) of the surfactant(s) associated with the metal nanoparticles. Thus, the surfactant(s) can be removed from the metal nanoparticles by evaporation before removal of the organic solvent(s) occurs.

[0048] In some embodiments, the organic matrix may contain one or more alcohols, and in more particular embodiments, the one or more alcohols may be C2-C 12 , C4~C 12 Or C7~C 12In various embodiments, the alcohol may include a monohydric alcohol, a diol, or a triol. In certain embodiments, one or more glycol ethers (e.g., diethylene glycol and triethylene glycol), alkanolamines (e.g., ethanolamine, triethanolamine, etc.), or any combination thereof may be present, either alone or in combination with other alcohols. In some embodiments, various glymes may be present with one or more alcohols. In some embodiments, one or more hydrocarbons may be present in combination with one or more alcohols. As discussed above, it is believed that the alcohols (and optionally the glymes and alkanolamines) and hydrocarbon solvents can passively promote solubilization of the surfactant as it is removed from the metal nanoparticles by Brownian motion, limiting reassociation of the surfactant with the metal nanoparticles. Furthermore, the hydrocarbon solvents and the alcohol solvents are only weakly coordinated to the metal nanoparticles, and do not simply replace the substituted surfactant in the nanoparticle coordination sphere. Illustrative, but non-limiting examples of alcohol and hydrocarbon solvents that may be present include, for example, light aromatic petroleum distillates (CAS 64742-95-6), hydrotreated light petroleum distillates (CAS 64742-47-8), tripropylene glycol methyl ether, ligroin (CAS 68551-17-7, C 10 ~C 13 Mixtures of alkanes), diisopropylene glycol monomethyl ether, diethylene glycol diethyl ether, 2-propanol, 2-butanol, t-butanol, 1-hexanol, 2-(2-butoxyethoxy)ethanol, and terpineol. In some embodiments, polyketone solvents can be used as well.

[0049] In some embodiments, the organic matrix may contain one or more amines and one or more organic acids. In some embodiments, the one or more amines and one or more organic acids may be present in an organic matrix that also includes one or more hydrocarbons and one or more alcohols. As discussed above, it is believed that the amines and organic acids may actively sequester surfactants that have been passively solubilized by the hydrocarbon and alcohol solvents, thereby making the surfactants unavailable for reassociation with the metal nanoparticles. Thus, organic solvents containing a combination of one or more hydrocarbons, one or more alcohols, one or more amines, and one or more organic acids may provide synergistic benefits for promoting compaction of metal nanoparticles. Illustrative, but non-limiting examples of amine solvents that may be present include, for example, tallow amine (CAS 61790-33-8), alkyl (C8-C 18 )Unsaturated amines (CAS 68037-94-5), di(hydrogenated tallow)amine (CAS 61789-79-5), dialkyl (C8-C 20 )Amine (CAS 68526-63-6), Alkyl (C 10 ~C 16 ) Dimethylamine (CAS 67700-98-5), Alkyl (C 14 ~C 18 ) dimethylamine (CAS 68037-93-4), dihydrogenated tallow methylamine (CAS 61788-63-4), and trialkyl (C6-C 12 ) amine (CAS 68038-01-7). Illustrative, but non-limiting examples of organic acid solvents that may be present in the nanoparticle paste composition include, for example, octanoic acid, nonanoic acid, decanoic acid, caprylic acid, pelargonic acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecanoic acid, palmitic acid, margaric acid, stearic acid, nonadecylic acid, alpha-linolenic acid, stearidonic acid, oleic acid, and linoleic acid.

[0050] In some embodiments, the organic matrix can include two or more hydrocarbons, two or more alcohols, optionally two or more glymes (glycol ethers), two or more amines, and two or more organic acids. For example, in some embodiments, each class of organic solvent can have two or more members, or three or more members, or four or more members, or five or more members, or six or more members, or seven or more members, or eight or more members, or nine or more members, or ten or more members. Furthermore, the number of members in each class of organic solvent can be the same or different. Specific advantages of using multiple members of each class of organic solvent are described below. Higher boiling organic solvents may provide safety advantages.

[0051] One particular advantage of using multiple members within each class of organic solvents is the ability to provide a wide range of boiling points in the metal nanoparticle paste composition. By providing a wide range of boiling points, the organic solvent can be gradually removed as the temperature increases, while affecting the compaction of the metal nanoparticles, thereby limiting volume shrinkage and favoring cracking. By gradually removing the organic solvent in this manner, less temperature control may be required to affect slow solvent removal than if a single solvent with a narrow boiling point range were used. In some embodiments, the members within each class of organic solvents are about 50% or more. o C ~ about 200 o C, or about 50 o C ~ approx. 250 o C, or about 100 o C ~ about 200 o C, or about 100 o C ~ approx. 250 o C, or about 150 o C ~ approx. 300 o C, or about 150 o C ~ approx. 350 o C, or about 150 o C ~ approx. 365 oIn more particular embodiments, the various members of each class of organic solvents each have a boiling point window that spans a range of at least about 20 o C, specifically about 20 o C~about 50 o C. More specifically, in some embodiments, each hydrocarbon can have a boiling point that is separated from the other hydrocarbons in the organic matrix by about 20. o C~about 50 o C, each alcohol has a boiling point that differs from the other alcohols in the organic matrix by about 20 o C~about 50 o C, each amine can have a boiling point that differs from the other amines in the organic matrix by about 20 o C~about 50 o C, each organic acid may have a boiling point that differs from the other organic acids in the organic matrix by approximately 20 o C~about 50 o C. The more members of each class of organic solvents present, the smaller the difference between the boiling points. By making the difference between the boiling points smaller, the solvent removal can be more continuous, thereby limiting the degree of volumetric shrinkage that occurs at each stage. When 4-5 or more members of each class of organic solvents are present, each with boiling points that are apart from one another within the above range (e.g., 4 or more hydrocarbons, 4 or more alcohols, 4 or more amines, and 4 or more organic acids; or 5 or more hydrocarbons, 5 or more alcohols, 5 or more amines, 5 or more organic acids), a reduced degree of cracking can occur.

[0052] In various embodiments, the metal nanoparticles used in the metal nanoparticle paste composition can be about 20 nm or less in size. In various other embodiments, the metal nanoparticles can be up to about 75 nm in size, or even up to about 200 nm in size, in at least one dimension. As mentioned above, metal nanoparticles in the size range of less than about 20 nm can have a melting temperature significantly lower than the melting point of the corresponding bulk metal, and as a result, are easily compacted together. In some embodiments, metal nanoparticles that are about 20 nm or less in size can be up to about 220 nm in size. o Melting temperature below C (e.g. about 140 o C ~ approx. 220 o C) or about 200 oC or less, thereby providing the above-mentioned advantages. In some embodiments, at least a portion of the metal nanoparticles can be about 10 nm or less in size, or about 5 nm or less in size. In more specific embodiments, at least a portion of the metal nanoparticles can be in a range of about 1 nm to about 20 nm in size, or about 1 nm to about 10 nm in size, or about 1 nm to about 5 nm in size, or about 3 nm to about 7 nm in size, or about 5 nm to about 20 nm in size. In some embodiments, substantially all of the metal nanoparticles can be present within these size ranges. In some embodiments, larger metal nanoparticles can be combined with metal nanoparticles of about 20 nm or less in size in the metal nanoparticle paste composition. For example, in some embodiments, metal nanoparticles in the range of about 1 nm to about 10 nm in size can be combined with metal nanoparticles in the range of about 25 nm to about 50 nm in size, or metal nanoparticles in the range of about 25 nm to about 100 nm in size, or metal nanoparticles in the range of about 25 nm to about 150 nm in size, or metal nanoparticles in the range of about 25 nm to about 200 nm in size. As discussed further below, in some embodiments, micron-scale metal particles, other micron-scale particles, and / or nanoscale particles can also be included in the metal nanoparticle paste composition. Larger metal nanoparticles and micron-scale metal particles may not be liquefiable at the low temperatures of their smaller counterparts, but can still be consolidated when in contact with smaller metal nanoparticles liquefied above the melting temperature, as outlined above.

[0053] Besides the metal nanoparticles and organic solvent, other additives may also be present in the metal nanoparticle paste composition. Such additional additives may include, for example, rheology control aids, thickeners, micron-scale conductive additives, nanoscale conductive additives, and any combination thereof. Chemical additives may also be present. As described below, it may be particularly advantageous to include micron-scale conductive additives, such as micron-scale metal particles. In some cases, it may be desirable to include nano- or micron-scale diamond or other thermally conductive additives to promote more efficient heat transfer and adjust the CTE. Suitable CTE adjusters, unless otherwise specified, may be in the form of particles or fibers, and may include, but are not limited to, carbon fibers, W particles, Mo particles, diamond particles, boron nitride, aluminum nitride, silicon nitride, copper oxide nanoparticles (e.g., about 2 nm to about 200 nm in size containing Cu2O and / or CuO), carbon nanotubes, graphene, graphite, and the like. Any of the aforementioned CTE adjusters may be micron-sized in at least one dimension.

[0054] In some embodiments, the paste composition can contain about 0.01% to about 15% by weight of micron-scale metal particles, or about 1% to about 10% by weight of micron-scale metal particles, or about 1% to about 5% by weight of micron-scale metal particles, or about 0.1% to about 35% by weight of micron-scale metal particles, or about 10% to about 60% by weight of micron-scale metal particles, or about 25% to about 55% by weight of micron-scale metal particles. The inclusion of micron-scale metal particles in the metal nanoparticle paste composition can desirably reduce the incidence of cracks that occur during consolidation of the metal nanoparticles to form the bulk metal. Without being bound by any theory or mechanism, it is believed that the metal nanoparticles are liquified and form a temporary liquid coating on the surfaces of the micron-scale metal particles, thereby allowing the micron-scale metal particles to consolidate together. In some embodiments, the micron-scale metal particles can range in size from about 500 nm to about 100 microns in at least one dimension, or from about 500 nm to about 10 microns in at least one dimension, or from about 100 nm to about 5 microns in at least one dimension, or from about 100 nm to about 10 microns in at least one dimension, or from about 100 nm to about 1 micron in at least one dimension, or from about 1 micron to about 10 microns in at least one dimension, or from about 5 microns to about 10 microns in at least one dimension, or from about 1 micron to about 100 microns in at least one dimension, or from about 1 micron to about 25 microns in at least one dimension, or from about 1 micron to about 5 microns in at least one dimension, or from about 5 microns to about 15 microns in at least one dimension. The micron-scale metal particles can contain the same metal as the metal nanoparticles, or can contain a different metal. Thus, by including micron-scale metal particles in a paste composition having a metal different from that of the metal nanoparticles, a metal alloy can be produced, i.e., a metal composite may in some cases include a metal alloy.Metal alloys may also be formed by combining different types of metal nanoparticles with each other. Suitable micron-scale metal particles may include, for example, Cu particles, Ni particles, Al particles, Fe particles, Co particles, Mo particles, W particles, Ag particles, Zn particles, Sn particles, Au particles, Pd particles, Pt particles, Ru particles, Mn particles, Cr particles, Ti particles, V particles, Mg particles, or Ca particles. Non-metallic particles such as, for example, Si micron-scale particles and B micron-scale particles may be used as well. In some embodiments, the micron-scale metal particles may be in the form of metal flakes, such as, for example, high aspect ratio copper flakes. Thus, in some embodiments, the metal nanoparticle paste composition described herein may contain a mixture of copper nanoparticles and high aspect ratio copper flakes or another type of micron-scale copper particles. Specifically, in some embodiments, the metal nanoparticle paste composition may contain about 30% to about 90% by weight of copper nanoparticles and about 0.01% to about 15% by weight or 1% to 35% by weight of high aspect ratio copper flakes. A CTE adjuster may also be present in the metal nanoparticle paste composition.

[0055] Other micron-scale metal particles that can be used equivalently to the high aspect ratio metal flakes include metal nanowires and other high aspect ratio particles, which can be, for example, about 300 microns or less in length. The ratio of metal nanoparticles to metal nanowires can be in the range of about 10:1 to about 40:1, according to various embodiments. Suitable nanowires can have lengths of, for example, about 5 microns to about 50 microns, and diameters of about 100 nm to about 200 nm, or about 100 nm to about 250 nm.

[0056] Additional materials that may also optionally be present in the metal nanoparticle paste composition include, for example, flame retardants, UV protection agents, antioxidants, carbon black, graphite, fibrous materials (e.g., chopped carbon fiber materials), diamond, and the like.

[0057] In some more specific embodiments, suitable nanoparticle paste compositions may include diamond particles or nanodiamond particles, which may be as large as possible in size to limit the grain boundaries that need to be crossed by phonons during heat transfer, while remaining small enough so as not to impair the dispersibility of the metal nanoparticle paste composition.

[0058] In yet more specific embodiments, diamond particles suitable for use in the metal nanoparticle paste composition may have a size in the range of about 1 micron to about 1000 microns, or about 0.5 microns to about 500 microns, or about 1 micron to about 10 microns, or about 2 microns to about 50 microns, or 50 microns to about 150 microns, which can provide good particle dispersion and acceptable paste dispersibility. Diamond particles having a size in the range of about 200 microns to about 250 microns or in the range of about 1 micron to about 10 microns can represent a good compromise between providing effective dispersion and minimizing grain boundaries to suppress phonon scattering. Other suitable size ranges for diamond particles can be in the range of about 25 microns to about 150 microns, or about 50 microns to about 250 microns, or about 100 microns to about 250 microns, or about 100 microns to about 200 microns, or about 150 microns to about 250 microns, or about 1 micron to about 100 microns, or about 10 microns to about 50 microns, or about 5 microns to about 25 microns.

[0059] In an exemplary embodiment, the metal composite may include about 10% to about 75% by volume of diamond particles after metal nanoparticle consolidation to form a monolithic metal body. Other conductive particles or CTE modifiers may be present in the same composition range. In some embodiments, one or more CTE modifiers may be present at 35% or about 60% by weight of the metal composite of the present disclosure.

[0060] The mixture of copper nanoparticles and diamond particles may be desirable for several reasons. Copper is low cost compared to most other metals, has a relatively good impedance match with diamond, and has a high thermal conductivity by itself. In some embodiments, the impedance match can be further improved by including a carbide-forming additive to form a thin layer of metal carbide (a monoatomic layer about 10 nm or less thick or a monoatomic layer about 50 nm or less thick) on the diamond particles. Suitable carbide-forming metals may include, for example, Ti, Zr, Hf, Cr, Mo, W, V, Mn, Fe, and any combination thereof. Thus, the combination of copper nanoparticles and diamond particles can provide very effective heat transfer in various embodiments of the present disclosure. Copper also provides high electrical conductivity to establish electronic communication between various substrate layers. Depending on the particular composition utilized, for example due to the amount of non-conductive additive, the electrical conductivity may be about 30-50% IACS, or about 35-60% IACS, or about 50-75% IACS, or about 55-90% IACS, or about 60-98% IACS (International Annealed Copper Standard).

[0061] Nanoparticle paste compositions suitable for use according to the present disclosure can be formulated using any of the metal nanoparticle paste compositions described herein above. Additionally, according to some embodiments, multiple metals may be present in the metal nanoparticle paste composition. In some or other embodiments, suitable metal nanoparticle paste compositions can include a mixture of metal nanoparticles, other nano-sized particles (i.e., particles having dimensions of about 200 nm or less), and / or micron-scale particles, such as micron-scale metal particles. Metal nanoparticle paste compositions can include copper nanoparticles according to more specific embodiments. In some embodiments, copper nanoparticles can be the major component (>50 wt%) of the metal nanoparticle paste composition.

[0062] Various heat spreaders and printed circuit boards utilizing heat spreaders may be formed, at least in part, from copper nanoparticles and copper nanoparticle paste compositions. In particular, copper nanoparticles or copper nanoparticle paste compositions may be utilized to manufacture at least a surface portion of a heat spreader. For example, a copper nanoparticle paste composition including a CTE modifier may be consolidated to form at least a partial coating on a thermal conductor, which coating may perform various functions described herein, or the copper nanoparticle paste composition may be consolidated to form the thermal conductor itself. It is understood that alternative metal nanoparticles may be utilized to form the conductors or coatings on the conductors that define the heat spreader, as needed to facilitate CTE matching to some ceramic materials within the heat generating component. Thus, it is understood that any embodiment utilizing copper or copper nanoparticles in the disclosure that follows may utilize alternative metals or metal nanoparticles (optionally in combination with copper) as per application specific needs, unless otherwise specified.

[0063] Similarly, the copper nanoparticle paste composition may be applied as a bonding layer between a heat generating component and a heat spreader containing the copper composite on at least a surface thereof. Following consolidation of the metal nanoparticles, the resulting bulk metal may provide a CTE-matched bonding interface between the heat generating component and the surface of the heat spreader (also formed from the consolidated metal nanoparticles). The bonding layer may form a full or partial coating on at least one side of the heat spreader in some embodiments. The bonding layer may be multi-layered in some embodiments, with each layer having a different CTE. The bonding layer may be metallurgically bonded to the heat spreader, but not necessarily bonded to the heat generating component. In any case, the bonding layer may have a CTE intermediate between the CTE of the heat generating component and the CTE of the heat spreader. A similar bonding layer may be interposed between the heat spreader and a heat sink or similar heat receiving structure, and the heat spreader may optionally be metallurgically bonded to the heat sink or similar heat receiving structure, and the bonding layer may have a CTE that is intermediate between the CTE of the heat spreader and the CTE of the heat sink or similar heat receiving structure, such as a heat pipe.

[0064] The heat spreader of the present disclosure may include a thermal conductor configured to contact a heat source and a heat sink, with at least a portion of the thermal conductor being CTE-matched to the heat generating component. In particular, at least a portion of the thermal conductor, a full or partial coating on the thermal conductor, or an interface material (bonding layer) between the thermal conductor and the heat generating component may include a copper composite with a CTE modifier, as further described herein. The thermal conductor may be a monolithic block that may include a metal, a metal alloy, or a metal composite. The thermal conductor may define a tapered heat spreader. The tapering of the heat spreader may distribute heat at its cold end and reduce the thermal load per unit area at this location. Various heat spreader configurations are defined below with reference to the drawings.

[0065] In various embodiments, the copper composite may be formed by consolidation of copper nanoparticles with micron-sized copper particles and a CTE modifier, or consolidation of copper nanoparticles with a CTE modifier without micron-scale copper particles. The copper nanoparticles, micron-sized copper particles (if present), and CTE modifier may define a copper nanoparticle paste composition, as set forth in more detail above. The copper nanoparticle paste composition may be utilized to form a thermal conductor of a heat spreader, a coating on a thermal conductor of a heat spreader, or may be utilized as a bonding interface material between a heat spreader and a heat generating component. A suitable copper nanoparticle paste composition may include about 30% to about 60% by weight of copper nanoparticles, about 5% to about 50% by weight of micron-sized copper particles, and an effective amount of a CTE modifier to target a particular CTE. The CTE modifier may be present in an amount ranging from about 1% to about 35% by weight, or from about 4% to about 8% by weight, or from about 5% to about 15% by weight, or from about 10% to about 20% by weight, or even about 35% or about 60% by weight. There may be more than one CTE modifier, such as two, three, four, or five or more different CTE modifiers. Micron-sized copper particles may be excluded in some embodiments.

[0066] Suitable CTE modifiers may include, but are not limited to, graphite / pitch-based carbon fibers (e.g., having a diameter of 10 microns), W particles, Mo particles, diamond particles, boron nitride particles or fibers, aluminum nitride particles or fibers, silicon nitride particles or fibers, carbon nanotubes, graphene, graphite powder, and the like, and any combination thereof. Unless otherwise specified, the CTE modifier may be in one or more forms of powder, particles, fibers, flakes, and the like. The amount of CTE modifier may be selected to provide the desired degree of CTE matching. For example, a carbon-based additive can achieve a thermal expansion of about 2-3 ppm when added at about 16 vol.%, or can achieve a thermal expansion of about 7 ppm when added at about 9 vol.%, or can achieve a thermal expansion of about 6 ppm when added at about 11 vol.%. A diamond addition of about 45 vol.% can achieve a thermal expansion of about 5-6 ppm depending on the density (82%). At about 37% volume loading and 93% density, the thermal expansion provided by diamond can be about 6 ppm. At diamond loadings greater than about 50% volume, the thermal expansion drops to less than about 5 ppm.

[0067] CTE modifiers can also, in some cases, significantly increase thermal conductivity. For example, carbon nanotubes can increase the thermal conductivity of copper from a low of 400 W / m·K for bulk copper alone to about 600 W / m·K. The degree of thermal conductivity tuning achievable with carbon nanotubes can depend on the length of the carbon nanotubes, with longer carbon nanotubes exceeding thermal conductivity values ​​of about 600 W / m·K.

[0068] The consolidated copper nanoparticles themselves exhibit a thermal expansion of about 7-12 ppm depending on the process conditions and density. As the density increases, the thermal expansion approaches that of bulk copper (17 ppm). At a density of about 91%, the thermal expansion is about 7-8 ppm, and at a density of about 93%, the thermal expansion increases to about 10-11 ppm. At a density of about 98%, the thermal expansion reaches about 12 ppm. Even at such high density values, the thermal expansion is still below that of bulk copper, which is presumed to be due to the nanoporosity present after copper nanoparticle consolidation.

[0069] The addition of micron-scale metal particles to metal nanoparticles (e.g., copper nanoparticles) can increase the thermal expansion to reach 17 ppm or more depending on the particular metal. For example, the addition of Al particles, which have a bulk CTE of about 23-24 ppm, can increase the CTE of the resulting composite to values ​​exceeding that of bulk copper. The addition of about 55% micron-scale copper powder results in a thermal expansion of about 14 ppm at 96% density.

[0070] The thermal conductor of the heat spreader disclosed herein may comprise a monolithic block of metal, metal alloy, or metal composite. When the thermal conductor comprises a metal composite, the additional components within the metal composite, such as CTE modifiers, diamond particles, or other types of particles with high thermal conductivity, may be distributed throughout the thermal conductor such that no portion of the thermal conductor is devoid of the additional components. That is, the thermal conductor does not include a compositional discontinuity where the additional components, such as CTE modifiers, are not present within a portion of the thermal conductor. Thus, the additional components, such as CTE modifiers, may be uniformly distributed in concentration within the thermal conductor, or may vary in concentration in a continuous or step gradient manner. The thermal conductor may increase in size from a "hot" end that contacts the heat generating component to a "cold" end that is configured to dissipate heat to a heat sink or other thermal reservoir, such as a radiator to the ambient atmosphere, marine environment, or external space. The loading of the additional components may increase or decrease in concentration from the hot end to the cold end in the heat spreader configurations disclosed herein.

[0071] In some embodiments, the heat spreader may include a multi-layer interface that promotes a gradual CTE change in a gradient or step-wise manner. The amount of CTE modifier and / or the composition of the CTE modifier in each layer of the multi-layer interface may be adjusted to provide a desired degree of CTE difference between each layer. A step or gradient change in CTE may provide less thermal stress between the heat generating component and the heat spreader than if there was a more abrupt CTE change at the interface between the two. Any number of layers may be present in the multi-layer structure, such as 2, 3, 4, 5, 6, 7, 8, 9, or 10 layers. Each layer may range from about 1 micron to about 25 microns in thickness, or from about 5 microns to about 10 microns in thickness. The CTE may vary between each layer by an amount ranging from about 1 ppm to about 2.5 ppm, or from about 0.8 ppm to about 1.5 ppm, or from about 1 ppm to about 2 ppm, or from about 1.5 ppm to about 2.2 ppm. For example, the CTE may be graded from 4 ppm in the heat generating component (e.g., containing SiC) to 17 ppm in the heat spreader through 5 layers having sequential CTEs of about 6.0 ppm, 8.2 ppm, 10.5 ppm, 12.8 ppm, and 15.0 ppm, or through 10 layers having sequential CTEs of about 5 ppm, 6.1 ppm, 7.3 ppm, 8.7 ppm, 10.1 ppm, 11.5 ppm, 12 ppm, 13.7 ppm, 14.9 ppm, and 16 ppm. The multilayer interface may optionally be present as a bonding layer on the surface of the heat spreader.

[0072] The heat spreaders disclosed herein may be of any specified shape. Without limitation, the heat spreaders may be circular, prismatic, oval, triangular, flat, oblate, etc. The heat spreaders may be tapered or non-tapered. If tapered, the heat spreader may increase in size from the hot end to the cold end. The tapering may be continuous or discontinuous.

[0073] 3A-3D show cross-sectional views of various configurations of heat spreaders of the present disclosure. In FIG. 3A, heat spreader 300 includes a thermal conductor 310 and a coating 312 disposed continuously on thermal conductor 310. At least a portion of coating 312 may include a metal composite suitable for CTE matching according to the disclosures herein. Alternatively, the thermal conductor may include a metal composite suitable for CTE matching according to the disclosures herein, but a separate metal composite coating may not be present. If present, coating 312 does not necessarily have to be a continuous coating as shown in FIG. 3A. FIG. 3B shows a diagram of heat spreader 301 in which coating 312 is discontinuous on thermal conductor 310. The discontinuous coating shown in FIG. 3B may be utilized to form a thermal connection and / or bond to a heat generating component (not shown). When disposed as a discontinuous coating, the discontinuous coating may be interposed between at least a portion of the space between the heat generating component and thermal conductor 302. The metal nanoparticle paste composition may be disposed in the space between the heat generating component and the thermal conductor 302 to provide a bonding layer therebetween.

[0074] The heat spreaders of the present disclosure may be tapered to provide more effective heat spreading. In FIG. 3C, heat spreader 302 includes a continuously tapered thermal conductor 310 having a coating 312 disposed on at least a portion of the thermal conductor 310, and in FIG. 3D, heat spreader 303 includes a discontinuously tapered thermal conductor 310 having a coating 312 disposed on at least a portion of the thermal conductor 310. Again, the coating 312 may be formed by consolidating a metal nanoparticle paste composition including a CTE modifier between the thermal conductor 310 and the heat generating component, thus establishing a bonding layer between the two. In both heat spreaders 302 and 303, surface 314 may contact a heat source (heat generating component) and surface 316 may contact or be in thermal communication with a heat sink or similar heat receiving structure, e.g., a heat pipe (heat source and heat sink not shown in FIG. 3C and FIG. 3D). For example, surface 314 may be in contact with an electronic component that generates excess heat.

[0075] When the metal nanoparticle paste composition containing the CTE modifier is used to form the thermal conductor of the heat spreader, the metal nanoparticle paste composition may be added to a suitable mold or die, and the copper nanoparticles may then be consolidated to form a monolithic metal block containing the CTE modifier. The metal nanoparticle paste composition may be applied to a thermally conductive metal body to form a coating on the thermal conductor or to form a bonding layer between the thermally conductive metal body and the heat generating component, or the metal nanoparticle paste composition may be sandwiched between the thermally conductive metal body and the heat generating component, and the metal nanoparticles in the metal nanoparticle paste composition may be consolidated at this stage to form a metal composite, such as a copper composite containing the CTE modifier. Suitable conditions for processing the metal nanoparticle paste composition may include, for example, injection molding, hot pressing, or similar deposition and consolidation techniques. Localized heating of the metal nanoparticles may be performed during the deposition and consolidation process. Localized rapid heating to form the metal composite may be performed, for example, using a laser or Xe lamp in non-limiting embodiments. Desirably, the fusion of metal nanoparticles to form a metal composite can be effected in the absence of an inert or reducing atmosphere, especially when rapid heating is performed.

[0076] In some configurations, multiple conductive fibers may extend from one end of the heat spreader. FIG. 4 shows a diagram of an exemplary heat spreader 400 with multiple conductive fibers 402 extending from one end of the thermal conductor 310. When so configured, the conductive fibers 402 may provide a large surface area for dissipating conducted heat to a heat sink or similar thermal reservoir. In the configuration shown in FIG. 4, the thermal conductor 310 is formed from a metal composite containing a CTE modifier, and there is no separate coating thereon (e.g., coating 312). The metal composite is produced by consolidation of metal nanoparticles, as described in more detail above. Thus, the conductive fibers 402 may be incorporated into the thermal conductor 310 during formation of the thermal conductor 310, specifically by inserting the conductive fibers 402 into a metal nanoparticle paste composition formed into the shape of the conductor 310, and then consolidating the metal nanoparticles. It should be understood that, alternatively, the conductive fibers 402 may be bonded to the heat spreader 400 by consolidation of metal nanoparticles in a separate coating (if present). Other than the conductive fibers 402 extending from the thermal conductor 310 (or a coating thereon), the heat spreader 400 is similar to, and may be better understood by reference to, the heat spreaders 300-303 (FIGS. 3A-3D). Common reference numerals are used to indicate elements having similar structure and function. Thus, any of the heat spreaders 300-303 may similarly incorporate the conductive fibers 402 in a manner similar to that described with respect to the heat spreader 400.

[0077] To introduce the conductive fibers 402 into the heat spreader 400, an unconsolidated metal nanoparticle paste composition may first be applied to (or used to form) the thermal conductor 310, and then the conductive fibers 402 may be disposed within the unconsolidated copper nanoparticle paste composition. Following consolidation of the copper nanoparticles, the conductive fibers 402 may be securely fixed to the heat spreader 400 in a matrix of bulk copper and dispersed CTE modifier formed from the copper nanoparticle paste composition.

[0078] Suitable conductive fibers may include, but are not limited to, graphite fiber bundles, which may exhibit thermal conductivity values ​​more than twice that of bulk copper (e.g., 800-1100 W / m·K or 550-1200 W / m·K). Other suitable conductive fibers may include, but are not limited to, metal fibers (e.g., Al fibers or Cu fibers), diamond fibers, carbon nanotubes or carbon nanotube fibers, or any combination thereof. Suitable fiber lengths may be about 2-8 inches, depending on the flexibility of the fibers. Suitable fiber diameters may be about 5-50 microns, or about 5-10 microns, or about 5-20 microns, or about 30-50 microns. The fibers may also be in the form of a porous foam extending from the thermal conductor (or a coating thereon), in which case a cooling fluid, such as air or liquid, may pass through the pores of the foam and / or over or through the fibers to carry away excess heat.

[0079] The heat spreaders disclosed herein may be utilized to dissipate heat from heat generating components associated with a printed circuit board. The heat generating components may include ceramics such as, for example, Si (CTE=2.6 ppm), SiC (CTE=4.2 ppm), GaN (CTE=5.6 ppm), or AlN (CTE=4.5 ppm). In a non-limiting example, the CTE of the heat spreader may be approximately 1 / 2 the CTE of the heat generating component. + Within 50% or approximately + Within 25% or approximately + Within 20% or approximately + Within 15% or approximately + Within 10% or approximately + Within 5% or approximately + Within 4% or approximately + Within 3% or approximately + Within 2% or approximately + The thermal conductor of the heat spreader or a coating thereon may exhibit a CTE value at room temperature in the range of about 2 ppm to about 6 ppm, or about 3 ppm to about 7 ppm, or about 5 ppm to about 10 ppm, or about 10 ppm to about 15 ppm, or about 15 ppm to about 25 ppm.

[0080] Thus, in some embodiments, the present disclosure provides a heat dissipation system employing a heat spreader that can be CTE matched to a heat generating component and a heat sink or similar heat receiving structure. + 20%. The heat dissipation system may include a heat spreader having a thermal conductor, where at least a portion of the thermal conductor or a coating thereon includes a copper composite including a coefficient of thermal expansion (CTE) modifier such that the thermal conductor has a coefficient of thermal expansion (CTE) of about 3 ppm to about 7 ppm, a heat generating component in contact with a first surface of the thermal conductor, the heat generating component having a CTE of about 3 ppm to about 7 ppm, and a heat sink or heat pipe in contact with a second surface of the thermal conductor, the heat sink or heat pipe also formed from the copper composite including a coefficient of thermal expansion modifier and having a CTE of about 3 ppm to about 7 ppm. Optionally, the thermal conductor of the heat spreader may be metallurgically bonded to the heat sink or heat pipe while achieving the aforementioned CTE match. Heat dissipation systems having the aforementioned features may be used in conjunction with printed circuit boards and other electronic components that generate excess heat, in non-limiting examples.

[0081] The printed circuit board of the present disclosure may include a heat generating component disposed on or embedded within an electrically insulating substrate, and at least one heat spreader in thermal communication with the heat generating component, the at least one heat spreader being CTE matched to at least the heat generating component. The at least one heat spreader may be in thermal communication with the heat generating component through direct or indirect physical contact and bonding with the heat generating component. The electrically insulating substrate may also be thermally insulating, e.g., FR4, or thermally conductive, e.g., AlN or SiN. In various examples, the at least one heat spreader is a heat spreader of the present disclosure, at least a portion of which comprises a metal composite formed from metal nanoparticles and a CTE adjuster (e.g., a copper composite with a CTE adjuster). The at least one heat spreader may be bonded to the heat generating component directly through a thermal conductor, indirectly through a coating on the thermal conductor, or indirectly through a bonding layer that comprises a copper composite CTE matched to the heat generating component and at least a portion of the heat spreader.

[0082] It should be understood that printed circuit boards, as used herein, also refer equally to alternative structures that have similar heat dissipation problems, such as SIPs and packaged electronics.

[0083] The heat generating component may be disposed on a top surface of the electrically insulating substrate or embedded within a recess in the electrically insulating substrate. At least one heat spreader may be bonded to a top surface of the heat generating component or a bottom surface of the heat generating component, one or more heat spreaders may be bonded to a side surface of the heat generating component, or any combination thereof. Specific configurations are provided below.

[0084] FIG. 5 illustrates a diagram of a heat spreader bonded to a top surface of a heat generating component. As shown, PCB 600 includes an electrically insulating substrate 602 and a heat generating component 604 thereon. A heat spreader 606 is bonded to the top surface of heat generating component 604. Heat spreader 606 may be integrated into and / or part of an integrated circuit housing in some cases. Although not shown in FIG. 5, heat generating component 604 may be embedded within electrically insulating substrate 602 and heat spreader 606 may be placed on a surface of electrically insulating substrate 602.

[0085] FIG. 6 illustrates a diagram of a heat spreader bonded to the bottom surface of a heat generating component. In this configuration, the heat spreader 606 extends through a via defined in an electrically insulating substrate 602 of the PCB 700 and contacts the backside of the heat generating component 604. The via may be of a suitable size for the heat spreader 606 to extend through the via. The heat spreader 606 may increase in lateral size (increase in taper) after passing through the via. Although not shown in FIG. 6, the heat generating component 604 may be embedded within the electrically insulating substrate 602.

[0086] Heat spreaders may also be bonded to the top and bottom surfaces of the heat generating component, as shown in Figure 7. In PCB 800, heat spreader 606a is bonded to the top surface of heat generating component 604, and heat spreader 606b extends through electrically insulating substrate 602 and is bonded to the bottom surface of heat generating component 604. Although not shown in Figure 7, heat generating component 604 may be embedded within electrically insulating substrate 602.

[0087] FIG. 8 shows multiple heat spreaders bonded to the sides of a heat generating component. In FIG. 8, a top view of a PCB 900 is shown looking at the heat generating component 604 and heat spreader 606 on the top surface of an electrically insulating substrate 602. The heat spreader 606 is bonded to both sides of the heat generating component 604. Although two heat spreaders 606 are shown with side bonding in the PCB 900, it is understood that one or more heat spreaders 606 may be similarly bonded. Side bonding of the heat spreader 606 may facilitate stacking to multiple PCB layers. Although not shown, it is understood that there may also be upper and lower heat spreaders (see FIGS. 5-7).

[0088] Thus, PCBs incorporating the heat spreaders of the present disclosure may be single layer or multi-layer, according to various embodiments. Multi-layer PCBs can include individual layers that are stacked together to define vias and other board features.

[0089] In various embodiments, the bonding layer between the heat spreader and the heat generating component may include copper, may be formed from copper nanoparticles, and more specifically, may be formed from a copper nanoparticle paste composition containing other additives suitable for adjusting the CTE to match the CTE of the heat generating component. The CTE adjusters may include carbon fibers, diamond particles, boron nitride, aluminum nitride, silicon nitride, carbon nanotubes, graphene, graphite, copper oxide nanoparticles, and the like. Other additives may be present in the copper nanoparticle paste composition for ease of distribution and handling. The bonding layer may include a second copper composite, which may be CTE matched to the copper composite of the heat spreader as well.

[0090] Embodiments disclosed herein include the following.

[0091] A. Heat Spreader. The heat spreader includes a thermal conductor configured to contact a heat source and a heat sink, where at least a portion of the thermal conductor or a coating thereon includes a copper composite including a coefficient of thermal expansion (CTE) modifier.

[0092] B. a printed circuit board having a heat generating component disposed on or embedded within an electrically insulating substrate; at least one heat spreader in thermal communication with the heat generating component, the at least one heat spreader comprising: A printed circuit board comprising a thermal conductor, wherein at least a portion of the thermal conductor or a coating thereon comprises a copper composite including a coefficient of thermal expansion (CTE) modifier.

[0093] C. Heat Dissipation Systems. A heat dissipation system may include a heat spreader having a thermal conductor, where at least a portion of the thermal conductor or a coating thereon comprises a copper composite including a coefficient of thermal expansion (CTE) modifier such that the thermal conductor has a coefficient of thermal expansion (CTE) of about 3 ppm to about 7 ppm; a heat generating component in contact with a first surface of the thermal conductor, the heat generating component having a CTE of about 3 ppm to about 7 ppm; and a heat sink or heat pipe in contact with a second surface of the thermal conductor, the heat sink or heat pipe also formed from a copper composite including a coefficient of thermal expansion modifier and having a CTE of about 3 ppm to about 7 ppm. Optionally, the thermal conductor or a coating thereon is about 3 ppm to about 7 ppm of the CTE of the heat generating component. + Optionally, the thermal conductor or coating thereon may have a CTE within about 20% of the CTE of the heat sink or heat pipe. + It may have a CTE within 20. Optionally, the thermal conductor or a coating thereon may be metallurgically bonded to the heat generating component and / or heat sink or heat pipe via a bonding layer.

[0094] Each of embodiments AC may have one or more of the following additional elements in any combination.

[0095] Element 1: Copper composite is formed by consolidation of copper nanoparticles with micron-sized copper particles and a CTE modifier.

[0096] Element 1A: The copper composite is formed by consolidation of copper nanoparticles and a CTE modifier.

[0097] Element 2: The copper composite has a uniform nanoporosity of about 2% to about 30%.

[0098] Element 3: The CTE adjuster comprises particles or fibers selected from the group consisting of carbon, W, Mo, diamond, boron nitride, aluminum nitride, silicon nitride, carbon nanotubes, graphene, graphite, copper oxide nanoparticles, and any combination thereof.

[0099] Element 4: The heat spreader further comprises a plurality of thermally conductive fibers extending from at least a portion of the thermal conductor or coating thereon (if present).

[0100] Element 5: The thermal conductor is formed entirely from a copper composite containing a CTE modifier.

[0101] Element 6: The CTE modifier is distributed throughout the thermal conductor.

[0102] Element 7: The thermal conductor is tapered.

[0103] Element 8: The CTE modifier is present in a stepped or gradient concentration distribution in the copper composite.

[0104] Element 9: At least one heat spreader is bonded to the heat generating component via a bonding layer comprising a copper composite CTE matched to the heat generating component. Optionally, the CTE of the heat generating component and the CTE of the thermal conductor and / or coating thereon are less than about + 20% or less, or about + 10% or less, or + differ by less than 5%.

[0105] Element 10: The copper composite of the bonding layer has a uniform nanoporosity of about 2% to about 30%.

[0106] Element 11: A heat generating component is disposed on or embedded within a surface of an electrically insulating substrate, and at least one heat spreader is bonded to a top surface of the heat generating component, one or more heat spreaders are bonded to a side surface of the heat generating component, at least one heat spreader is bonded to a bottom surface of the heat generating component, at least one heat spreader extends through the electrically insulating substrate, or any combination thereof.

[0107] As a non-limiting example, exemplary combinations applicable to A through C include, but are not limited to, 1 or 1A, and 2; 1 or 1A, and 3; 1 or 1A, and 4; 1 or 1A, and 5; 1 or 1A, and 6; 1 or 1A, and 7; 1 or 1A, and 8; 2 and 3; 2 and 4; 2 and 5; 2 and 6; 2 and 7; 2 and 8; 3 and 4; 3 and 5; 3 and 6; 3 and 7; 3 and 8; 4 and 5; 4 and 6; 4 and 7; 4 and 8; 5 and 6; 5 and 7; 5 and 8; 6 and 7; 6 and 8; and 7 and 8. With respect to B and C, any of the foregoing may be further combined with 9, 10, or 11. Further exemplary combinations applicable to B and C include, but are not limited to, 9 and 10; 9 and 11; 10 and 11; and 9-11.

[0108] In order to facilitate a better understanding of the embodiments of the present disclosure, the following examples of preferred or representative embodiments are given. In no way should the following examples be read to limit or define the scope of the invention.

[0109] Working Example Example 1. To produce a solid cylinder 11.7 mm high and 0.5 inch wide, 2.7 mL of 5.1 g / ccm high density paste containing 43% (v / v) commercially available dried graphite powder, 24% (v / v) commercially available dried copper powder, and 33% (v / v) copper nanoparticles was placed into a 3 inch high by 2 inch wide graphite cell with a 0.5 inch hole closed at both ends with tightly fitted graphite rods. The cell was then placed in a hydraulic press. An initial pressure of 250 psi was applied while the cell was heated to 250° C. The pressure was increased to 500 psi at 100° C., 1000 psi at 200° C., 1750 psi at 250° C., and then maintained throughout the process. The target peak temperature was reached after approximately 15 minutes and maintained for an additional 75 minutes. The heat was then shut off, the cell was cooled to room temperature, and the part was extruded. The cylinder weighed 12.2 g and had a density of 92%.

[0110] Example 2. To produce a 6.8 mm tall, 0.5 inch wide solid cylinder, 1.6 mL of 4.9 g / ccm high density paste containing 33% (v / v) commercially available dry BN powder, 33% (v / v) commercially available dry copper powder, and 34% (v / v) copper nanoparticles was placed into a 3 inch tall by 2 inch wide graphite cell with a 0.5 inch hole closed at both ends with tightly fitted graphite rods. The cell was then placed in a hydraulic press. An initial pressure of 250 psi was applied while the cell was heated to 250° C. The pressure was increased to 500 psi at 100° C., 1000 psi at 200° C., 1750 psi at 235° C., and then maintained throughout the process. The target peak temperature was reached after approximately 10 minutes and maintained for an additional 45 minutes. The heat was then shut off, the cell was cooled to room temperature, and the part was extruded. The cylinder weighed 6.9 g and had a density of 90%.

[0111] Example 3. To produce a solid cylinder 15.6 mm high and 0.5 inch wide, 2.9 mL of 4.3 g / ccm high density paste containing 7% (v / v) commercially available dry diamond powder, 23% (v / v) commercially available dry copper powder, and 70% (v / v) copper nanoparticles was placed into a 3 inch high by 2 inch wide graphite cell with a 0.5 inch hole closed at both ends with tightly fitted graphite rods. The cell was then placed in a hydraulic press. An initial pressure of 250 psi was applied while the cell was heated to 250° C. The pressure was increased to 500 psi at 100° C., 1400 psi at 200° C., 1850 psi at 235° C., and then maintained throughout the process. The target peak temperature was reached after approximately 15 minutes and maintained for an additional 85 minutes. The heat was then shut off, the cell was cooled to room temperature, and the part was extruded. The cylinder weighed 11.7 g and had a density of 92%.

[0112] Additional specimens were prepared in a manner similar to that described above for Examples 1 to 3. The metal composite compositions and the CTE values ​​obtained from the metal composite compositions at various temperatures are shown in Table 1.

[0113] [Table 1]

[0114] Unless otherwise indicated, all numbers expressing quantities of ingredients, properties such as molecular weights, reaction conditions, and the like used in the specification and the related claims are to be understood as being modified in all instances by the term "about." Accordingly, unless otherwise indicated, the numerical parameters set forth in the following specification and appended claims are approximations that may vary depending upon the desired properties sought to be obtained by embodiments of the present invention. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.

[0115] One or more exemplary embodiments incorporating features of the present disclosure are presented herein. For clarity, not all features of a physical implementation are described or illustrated in this application. It should be understood that in developing a physical embodiment incorporating the present disclosure, numerous implementation-specific decisions must be made to achieve the developer's goals, such as compliance with system-related constraints, business-related constraints, government-related constraints, and other constraints that vary from implementation to implementation and from time to time. Although the developer's efforts may require significant time, such efforts would nevertheless be routine for those skilled in the art and who have the benefit of the present disclosure.

[0116] Thus, the present disclosure is well adapted to attain the objects and advantages mentioned, as well as those inherent therein. The particular embodiments disclosed above are illustrative only, as the disclosure may be modified and practiced in different but equivalent manners apparent to those skilled in the art having the benefit of the teachings herein. Moreover, no limitations are intended to the details of construction or design shown herein, other than as described in the following claims. It is therefore apparent that the particular exemplary embodiments disclosed above may be altered, combined or modified, and all such variations are deemed to be within the scope and spirit of the invention. The disclosure herein may suitably be practiced in the absence of any element not specifically disclosed herein and / or optional elements disclosed herein. Although the compositions and methods are described in terms "comprising," "containing," or "including" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and steps. All of the numbers and ranges disclosed above may be varied by some amount. Whenever a numerical range is disclosed with a lower and upper limit, any number falling within that range and any range encompassed therein are specifically disclosed. In particular, all ranges of values ​​disclosed herein (in the form of "from about a to about b," or equivalently, "from approximately a to b," or equivalently, "from approximately a to b") are to be understood to describe all numbers and ranges encompassed within the broader range of values. Additionally, the terms in the claims have their plain and ordinary meaning unless expressly and unambiguously defined by the patent owner. Additionally, the indefinite article "a" or "an," as used in the claims, is defined herein to mean one or more of the element it introduces.

Claims

1. 1. A heat spreader comprising:

1. A heat spreader comprising: a thermal conductor configured to contact a heat source and a heat sink, wherein at least a portion of the thermal conductor or a coating thereon comprises a copper composite including a coefficient of thermal expansion (CTE) modifier.

2. 2. The heat spreader of claim 1, wherein the copper composite is formed by consolidation of copper nanoparticles, micron-sized copper particles and the CTE modifier.

3. The heat spreader of claim 1 , wherein the copper composite has a uniform nanoporosity of about 2% to about 30%.

4. 2. The heat spreader of claim 1, wherein the CTE modifier comprises particles or fibers selected from the group consisting of carbon, W, Mo, diamond, boron nitride, aluminum nitride, silicon nitride, carbon nanotubes, graphene, graphite, copper oxide nanoparticles, and any combination thereof.

5. a plurality of thermally conductive fibers extending from at least a portion of the thermally conductive body or, if present, from the coating thereon; The heat spreader of claim 1 further comprising:

6. The heat spreader of claim 1 , wherein said thermal conductor is formed entirely from said copper composite including said CTE modifier.

7. The heat spreader of claim 6 , wherein the CTE modifier is distributed throughout the thermal conductor.

8. The heat spreader of claim 1 , wherein the thermal conductor is tapered.

9. The heat spreader of claim 1 , wherein the CTE modifier is present in the copper composite in a graded or gradient concentration distribution.

10. The heat spreader of claim 1 , wherein the copper composite has a CTE of about 3 ppm to about 7 ppm.

11. 1. A printed circuit board (PCB), comprising: a heat generating component disposed on an electrically insulating substrate or embedded in the electrically insulating substrate; at least one heat spreader in thermal communication with the heat generating component, the at least one heat spreader comprising: A printed circuit board (PCB) comprising a thermal conductor, at least a portion of the thermal conductor or a coating thereon comprising a copper composite including a coefficient of thermal expansion (CTE) modifier.

12. 12. The PCB of claim 11, wherein the copper composite is formed by consolidation of copper nanoparticles, micron-sized copper particles and the CTE modifier.

13. The PCB of claim 11, wherein the copper composite has a uniform nanoporosity of about 2% to about 30%.

14. 12. The PCB of claim 11, wherein the at least one heat spreader is bonded to the heat generating component via a bonding layer comprising a second copper composite CTE matched to the heat generating component.

15. The PCB of claim 14, wherein the second copper composite of the bonding layer has a uniform nanoporosity of about 2% to about 30%.

16. 12. The PCB of claim 11, wherein the CTE modifier comprises particles or fibers selected from the group consisting of carbon, W, Mo, diamond, boron nitride, aluminum nitride, silicon nitride, carbon nanotubes, graphene, graphite, copper oxide nanoparticles, and any combination thereof.

17. The PCB of claim 11 , wherein the thermal conductor is formed entirely from the copper composite including the CTE modifier.

18. The PCB of claim 17 , wherein the CTE modifier is distributed throughout the thermal conductor.

19. The PCB of claim 11 , wherein the thermal conductor is tapered.

20. 12. The PCB of claim 11, wherein the heat generating component is disposed on or embedded within a surface of the electrically insulating substrate, and wherein: the at least one heat spreader is bonded to a top surface of the heat generating component; The at least one heat spreader is bonded to a side surface of the heat generating component; the at least one heat spreader is bonded to a bottom surface of the heat generating component, the at least one heat spreader extending through the electrically insulating substrate; or any combination thereof.

21. The PCB of claim 11 , wherein the CTE modifier is present in the copper composite in a graded or gradient concentration distribution.

22. The PCB of claim 11, wherein the copper composite has a CTE of about 3 ppm to about 7 ppm.

23. 1. A heat dissipation system comprising: a heat spreader having a thermal conductor, at least a portion of the thermal conductor or a coating thereon comprising a copper composite including a coefficient of thermal expansion (CTE) modifier such that the thermal conductor has a coefficient of thermal expansion (CTE) of about 3 ppm to about 7 ppm; a heat generating component in contact with a first surface of the thermal conductor, the heat generating component having a CTE of about 3 ppm to about 7 ppm; a heat sink or heat pipe in contact with the second surface of the thermal conductor; The heat sink or heat pipe is also formed from the copper composite containing the thermal expansion coefficient modifier and has a CTE of about 3 ppm to about 7 ppm.

24. 24. The heat dissipation system of claim 23, wherein the thermal conductor or the coating thereon is metallurgically bonded to the heat sink or heat pipe via a bonding layer.

25. 24. The heat dissipation system of claim 23, wherein the thermal conductor or the coating thereon has a CTE within about +20% of the heat generating component.

Citation Information

Patent Citations

  • Semiconductor device

    JP1996130275A

  • Heat radiation system and method therefor, heat buffering member, semiconductor module, heat spreader, and substrate

    JP2004063655A

  • Method of manufacturing heat dissipation member

    JP2006269828A

  • Semiconductor device and its manufacturing method

    JP2006352080A

  • Substrate for mounting semiconductor element and semiconductor element device using the same

    JP2015099913A